Administración pública – gobernanza y seguridad ciudadana del Gobierno Autónomo Descentralizado Municipal del cantón Chone 2022 -2023 - Carvajal Reinoso, Bianca Valeria (2025)
This research focused on evaluating governance and citizen security at the Decentralized Autonomous Municipal Government in Chone Canton during the 2022–2023 period, with the purpose of identifying weaknesses and proposing improvement strategies. To achieve this, three phases were developed in alignment with the specific objectives of the study. First, an analysis of the current legal and regulatory framework was conducted, which revealed that, although there is a clear legal structure at the national level, at the local level there is a lack of specific ordinances to formally support the actions carried out by the municipal government. In the second phase, interviews and surveys were applied to diagnose the actual state of institutional management, identifying issues such as weak interinstitutional coordination, budget limitations, lack of strategic planning, and limited citizen participation. Finally, in the third phase, an Improvement Plan was designed with strategies aimed at regulatory institutionalization, financial strengthening, citizen participation, and technological modernization. It is concluded that the Decentralized Autonomous Municipal Government of Chone needs to strengthen its internal regulatory framework and management capacity in order to effectively respond to the challenges related to governance and citizen security.